The Sport Medicine Diagnostic Coding System - Meeuwisse, W. H.; Wiley, J. P. (Clinical Journal of Sport Medicine, 2007)
The Sport Medicine Diagnostic Coding System (SMDCS) was developed in 1991 in response to the need for a classification system that could capture detail relevant to sport-related injury. It employs a 6 character structure with 1 pair of digits for each of the body region, the structure, and the diagnosis. This format permits sorting of data on the basis of any pair of digits to allow analysis of the body region, the structure, and the diagnosis type. They can also be combined to search for unique diagnoses. These codes have been used in a clinical setting since inception and have also been used in studies on sport injury surveillance and injury prevention. A number of organizations currently use this system in their ongoing surveillance. With the publication of recent consensus statements on injury data collection in the sports of football (soccer) and rugby, the SMDCS has been updated with new data columns to "cross map" the SMDCS to the broader consensus categories. This manuscript is accompanied by a downloadable data file to enable other groups to use the SMDCS for their own purposes.